2000
DOI: 10.1111/j.1469-445x.2000.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Veni, vidi, vici: the neurohypophysis in the twentieth century

Abstract: We outline the key discoveries in the first 70 years of research on the neurohypophysis that provided the foundations for more recent studies in the last 30 years. We consider the extent to which these recent studies, which have exploited molecular technologies, cellular electrophysiological techniques and mechanistic behavioural investigations, have advanced or changed our understanding of the functions of oxytocin and vasopressin. The different evolutionary pressures on the oxytocin and vasopressin systems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Vasopressin and oxytocin derived from magnocellular neurons (Russell and Leng,2000) are transported together with their neurophysin carriers, neurophysin I and II (Fotheringham et al,1991; Trembleau et al,1994), in neurosecretory vesicles along the axon toward the neurohypophysis for secretion (Dreifuss,1975; Brownstein et al,1980). Axonal transport involves the formation of neurophysin–vasopressin complexes attached to the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin and oxytocin derived from magnocellular neurons (Russell and Leng,2000) are transported together with their neurophysin carriers, neurophysin I and II (Fotheringham et al,1991; Trembleau et al,1994), in neurosecretory vesicles along the axon toward the neurohypophysis for secretion (Dreifuss,1975; Brownstein et al,1980). Axonal transport involves the formation of neurophysin–vasopressin complexes attached to the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The story of oxytocin and vasopressin (5) began in 1895, when Oliver and Schafer reported that extracts of the posterior pituitary gland could affect urine flow, although what they described was a diuretic rather than an antidiuretic effect. In 1906, Dale reported that such extracts could also promote uterine contractions, and soon after, effects on mammary secretion were reported but confusion about the renal effects persisted.…”
Section: Introductionmentioning
confidence: 99%
“…The magnocellular neurones of the supraoptic (SON) and paraventricular (PVN) nuclei of the hypothalamus are the major sites of synthesis of the nonapeptide hormones vasopressin (VP) and oxytocin (OT) and their associated neurophysin (NP) carrier proteins (Vandesande & Dierickx, 1975). These neuronal systems are highly homologous, both projecting from the same hypothalamic nuclei through the internal zone of the median eminence to the posterior pituitary gland, from where the hormones are released, in response to physiological cues, into the peripheral circulation (Robinson, 1986; Russell & Leng, 2000). These anatomical characteristics make them an excellent model system in which to study the physiological regulation of hypothalamo‐pituitary secretion.…”
mentioning
confidence: 99%
“…Magnocellular OT stimulates the contraction of myoepithelial cells in the mammary gland to cause milk ejection during suckling (Bisset, 1974). OT is also a potent uterotonic agent and plays a role in normal parturition (Russell & Leng, 2000). In addition to the neuroendocrine magnocellular cells, OT and VP are also expressed in parvocellular cells in regions of the CNS (Caffé et al 1987) where they may act as neurotransmitters or neuromodulators (de Wied et al 1993) involved in the stress axis, circadian rhythms, temperature, motor responses or reproduction‐related behaviours (Pedersen et al 1982; Rivier & Vale, 1983; Burnard et al 1984; Kasting, 1989; Winslow et al 1993; Watanabe et al 2000).…”
mentioning
confidence: 99%